2023
DOI: 10.7759/cureus.47161
|View full text |Cite
|
Sign up to set email alerts
|

An Insight Into Tuberculosis Patients in the Chest Clinic of North India: Epidemiological Profile and Treatment Outcomes in the Wake of COVID-19

Saran Singh,
Shweta Gupta,
Abhinav Jha
et al.

Abstract: Our study aims to re-evaluate the epidemiological profile and treatment outcomes of TB patients enrolled at the chest clinic of a tertiary care center after the third wave of COVID-19 in New Delhi. Patients and methodsWe have conducted an observational analytical study after taking the IEC approval from October 2022 to February 2022 on the TB patients enrolled from March 2022 to August 2022. The total data of 1114 TB patients was analyzed. The association between various factors and treatment outcomes was asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…Through the analysis of the demographic characteristics of patients with double infection, it was found that the age of HIV/AIDS patients with PTB infection was mainly concentrated in 30~60 years old, mainly middleaged and young people, and there were more males than females. This conclusion was similar to the results of a study in New Delhi, which found in the investigation of tuberculosis patients: Men, HIV-TB co-infected, the elderly, people with tuberculosis and MDR-TB were at higher risk of death [17] . This may be because adult men mostly work outside, the number of male extramarital partners, and the proportion of voluntary sex are higher than women, and in some areas with a high burden of HIV, women do not know the HIV status of male partners and are infected with HIV without knowledge; the rising proportion of men who have sex with men, particularly within the elderly group, is contributing to an increase in the rate of HIV infection among the elderly [18] .…”
Section: Discussionsupporting
confidence: 91%
“…Through the analysis of the demographic characteristics of patients with double infection, it was found that the age of HIV/AIDS patients with PTB infection was mainly concentrated in 30~60 years old, mainly middleaged and young people, and there were more males than females. This conclusion was similar to the results of a study in New Delhi, which found in the investigation of tuberculosis patients: Men, HIV-TB co-infected, the elderly, people with tuberculosis and MDR-TB were at higher risk of death [17] . This may be because adult men mostly work outside, the number of male extramarital partners, and the proportion of voluntary sex are higher than women, and in some areas with a high burden of HIV, women do not know the HIV status of male partners and are infected with HIV without knowledge; the rising proportion of men who have sex with men, particularly within the elderly group, is contributing to an increase in the rate of HIV infection among the elderly [18] .…”
Section: Discussionsupporting
confidence: 91%